Enhancing material properties with a sustainable wood-quartz-HDPE composite: a study on strength - Vishalagoud S. Patil; Arun Y. Patil; Piyush Kumar; Anil Kumar; Raman Kumar; Chander Prakash; P. C. Arunakumara; Mallikarjungouda B. Patil; Keshavamurthy R.; Jaber M. Asiri; Yunus Khan T. M.; Shaik Mohamed Shamsudeen (Cogent Engineering)
Currently, the world is focusing on sustainable development aspects to maintain a healthy environment for future generation, and it is mandatory that researchers consider naturally available resource utilization in the form of waste. However, one concern with natural resources is their low strength in terms of their mechanical and physical properties. Here, we attempt to combine wood-quartz-HDPE as a rare combination to fulfil all the current material requirements. As the amount of quartz percentage increased from 20% to 40% has major influence in enhancing the properties such as tensile strength, compressive strength, impact strength and hardness. The study revealed interesting aspects, such as cracks and voids that were filled with quartz powder to bond with wood and High-Density Polyethylene (HDPE) powder to form a cluster of high strength materials. The outcomes show potential for the possible replacement for the existing material where degradability and recycling are the major concern. However, future work is recommended to study the behavior of materials in terms of fatigue and fracture mechanics to realize its durability and sustainability.